2022
DOI: 10.18203/issn.2455-4529.intjresdermatol20222726
|View full text |Cite
|
Sign up to set email alerts
|

Management of skin and soft-tissue infections and acne with topical nadifloxacin: a comprehensive review

Abstract: <p class="abstract">Skin and soft tissue infections (SSTIs) and acne are multi-factorial skin conditions that involve microbial invasion of the skin and underlying soft tissues; though, both have different pathogenesis. Most of these infections are caused by bacteria, affecting all age groups. Early diagnosis and appropriate antimicrobial therapy remain the cornerstone of management of SSTIs and acne. Over the years, an increase in antibiotic resistance has been reported with mupirocin and fusidic acid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Healthcare practitioners may successfully treat bacterial infections while avoiding antimicrobial resistance with this medication. 3,4 Previous in vitro research on bacterial skin infections showed that Nadifloxacin is safe and effective against a range of bacteria. It's very effective against Streptococcus and Propionibacterium species.…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare practitioners may successfully treat bacterial infections while avoiding antimicrobial resistance with this medication. 3,4 Previous in vitro research on bacterial skin infections showed that Nadifloxacin is safe and effective against a range of bacteria. It's very effective against Streptococcus and Propionibacterium species.…”
Section: Introductionmentioning
confidence: 99%